Research trends in the study of biofilms related to periodontal disease: A bibliometric analysis - Julio C. Romero-Gamboa; Melissa Pinella-Vega; Pablo A. Millones-Gómez; John E. Gallego-Ramírez; Alejandro Valencia-Arias (GarVal Editorial Ltda., 2024)
Context: The study of biofilms in the context of periodontal diseases is of paramount importance due to their central role in the pathogenesis of these oral diseases. Research has focused on understanding the formation, structure, and dynamics of biofilms, as well as developing therapeutic approaches for their eradication. However, there are still conceptual gaps in the scientific literature due to a lack of review studies. Aims: To examine research trends in the study of biofilms related to periodontal diseases. Methods: This study used a bibliometric analysis methodology of scientific literature based on the PRISMA-2020 statement. Results: The results showed a remarkable increase in research activity in recent years. Prominent authors, influential journals, and emerging keywords such as "multispecies biofilm", "biofilm formation" or "periodontal therapy" were identified, reflecting the areas of greatest interest. Conclusions: The need to balance the exploration of new areas with the consolidation of other key concepts is highlighted, as well as gaps in research that require more precise therapeutic approaches, longitudinal studies, and greater attention to underserved communities in developing countries.